“I AM NOT FULLY MEDICALIZED.”: A QUALITATIVE STUDY OF POST-NATAL CARE AMONG MALAYSIAN CHILD-BIRTHING WOMEN IN THE UNITED KINGDOM (Proceedings of the Global Public Health Conference, 2021)
Obstetric medicine and reproductive technology have been spread outworldwide and become the symbol of modernization. Its expansion might displace thetraditional treatments which mostly are practiced by the people in developing countries.However, the Malaysian women who lived in a Western country and had a well-educatedbackground still practiced the traditional treatments after giving birth. The study wasconducted in 2016 at Durham, a county in the United Kingdom, and it utilized qualitativeresearch by interviewing five Malaysian women who had a birth experience in the UnitedKingdom. The result of the study revealed that heating the body with hot stone has stillmostly practiced by Malaysian women even living in the United Kingdom, where therewere optional sophisticated technology and qualified medical professional. In addition,some of them still obeyed the recommended and prohibited foods ruled by the originculture during the postpartum period. The treatment was conducted at home supported bythe family and colleagues whose the same ethnicity and nationality. In conclusion, thenational boundaries, high education, and the existence of sophisticated health technologyand qualified medical professional are irrelated to why people still undertake traditionaltreatments. The treatment was primarily chosen because of its health effects on the bodyafter treatments. Therefore, health policymakers have to know and consider the migrant‟scultural values in order to make the health system convenient and appropriate to either themigrants‟ health. In addition, the study needs further research to find the effectiveness andefficacy of traditional treatments to women‟s health.
Keywords: traditional treatments; postpartum period; humoral system; heat therapy; cultural value; Malaysian culture